Intervención grupal para ayudar en la generación de recursos resilientes en mujeres adultas víctimas de violencia intrafamiliar en el centro de equidad y justicia en la administración sur Eloy Alfaro - Silva Tapia, Estefanía Margarita (2016)
This work contains the systematization of a group intervention at the “Eloy Alfaro” Equity and Justice Center, regarding to the generation of resilient resources in adult women who have been victims of domestic violence. This systematization focuses on the intervention process conducted over a period of six months with the participants, about the development and strengthening of four pillars: external support, inner strength, interpersonal factors and new signifiers of gender roles. It was used a categorical qualitative analysis of the experience recorded in the way of field diaries, in order to classify the obtained material and then relate it with the theory. This concludes with the fact that the analyzed factors were strengthened after the intervention process and that there was a positive influence on personal and group dynamics.